A Study of the Influence of First Aid Education and RICE Protocol on Athletes - Devalani Twenty Novita; Mustiah Yulistiani (UM Purwokerto Press, 2024)
Background: Injuries during training, sports activities, or after competitions are called sports injuries. Among the Injuries experienced by Merpati Putih athletes, there were 19 cases of bruising, five cases of dislocation, 23 cases of muscle cramps, two cases of bone fractures, and six students who did not experience any injuries. Method: The research design used in this study was pre-experimental with the One-group Pretest-Posttest Design approach. The total sample size was 37 respondents. The research instruments utilized questionnaires and Standard Operating Procedures (SOP). The data analysis employed the Wilcoxon statistical test. Results: There was an increase in the average level of knowledge and skills before and after. The results revealed a P-value of 0.001 for the knowledge level and a P-value of 0.001 for the skill level. Both sets of statistical data indicated that P0.05. Conclusion: There is on effect of First Aid Education on Sports Injury with RICE on the risk of sports injury towards the knowledge and skills level of Merpati Putih athletes.